Preparation method of quinary copolymerized high-Tg polyimide film
A five-component copolymer high Tg polyimide film addresses the limitations of existing films by enhancing molecular chain rigidity and alignment, achieving superior thermal stability and mechanical properties for flexible display substrates.
Patent Information
- Application Number
- CN202411156015.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-08-22
AI Technical Summary
Existing polyimide films have glass transition temperatures (Tg) that do not exceed 400°C, limiting their use in flexible display substrates due to insufficient heat resistance and thermal dimensional stability, leading to issues like creep and structural instability under bending.
A five-component copolymer high Tg polyimide film is prepared using p-phenylenediamine, pyromellitic dianhydride, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diaminodiphenyl ether, and 3,3',4,4'-biphenyltetracarboxylic dianhydride, with controlled reaction conditions to enhance molecular chain rigidity and alignment, resulting in a film with high Tg, tensile strength, and thermal stability.
The prepared film achieves a glass transition temperature of up to 540°C, providing excellent mechanical properties with high tensile strength and elongation, suitable for flexible packaging applications.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyimide films, and in particular relates to a method for preparing a five-component copolymer high-Tg polyimide film. Background Art
[0002] Since its advent, polyimide (PI) has been widely synthesized and used in microelectronic devices, films and adhesives due to its excellent mechanical properties, high thermal stability, low dielectric constant and easy processing. However, in the rapidly developing field of flexible display substrates, there is an urgent need to develop polyimide (PI) with high heat resistance and high thermal dimensional stability. Because, in the processing of flexible display devices, the actual processing temperature is generally around 400-500°C, which puts higher requirements on the glass transition temperature (Tg) of PI as a flexible substrate. For example: polyimide used for AMOLED flexible substrates is generally higher than 430°C; for PI used in flexible printed circuit boards, the higher the Tg value, the better. When Tg>400°C, it will significantly help improve the packaging performance of flexible printed circuit boards and expand the field of use.
[0003] The glass transition temperature of existing polyimide films generally does not exceed 400°C. Polyimide films are ideal cover materials for advanced flexible AMOLED displays. If low-Tg polyimide films are used on cover plates for a long time, the cover plates will creep after long-term static or dynamic bending, and will not be able to maintain excellent structural stability. In the conventional methods for preparing high-Tg polyimide films, it is difficult to achieve high Tg due to the strong rigidity of the PI molecular chain and the difficulty of thermal stretching, which seriously affects the heat resistance and high thermal dimensional stability of the polyimide films. Summary of the invention
[0004] In view of the above shortcomings, the present invention discloses a method for preparing a five-component copolymer high Tg polyimide film, which produces a high Tg polyimide film with good heat resistance and high thermal dimensional stability, and promotes the application of polyimide film products in the field of flexible display substrates.
[0005] The present invention is achieved by adopting the following technical solutions: A method for preparing a five-component copolymer high Tg polyimide film comprises the following steps: (1) weighing raw materials according to the molar ratio of p-phenylenediamine (PDA), pyromellitic dianhydride (PMDA), 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE), 4,4'-diaminodiphenyl ether (ODA) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) of (1.0-1.5):(4-5):(2-3):(1.5-1.8):(0.5-3) and placing them in an oven for drying respectively; dividing pyromellitic dianhydride (PMDA) into three parts of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C, and the mass ratio of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C is 2:3:5; Take p-phenylenediamine (PDA) and dissolve it in an organic solvent and stir to obtain a diamine monomer solution. Add dianhydride monomer A to the diamine monomer solution and stir and react for 0.5 hours to obtain a mixed solution. Then, add 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE) to the mixed solution and stir and react for 0.5 hours. Then, add dianhydride monomer C and stir and react for 0.5 hours. Then, add 4,4'-diaminodiphenyl ether (ODA) and stir and react for 0.5 hours. Then, add dianhydride monomer B and stir and react for 0.5 hours. Finally, add 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (S-BPDA) to adjust the viscosity, and stir and react in a cold water bath to obtain a polyamic acid solution (PAA). (2) The polyamic acid solution obtained in step (1) is coated on a glass plate, and then the temperature is increased for thermal imidization to obtain a high Tg polyimide film.
[0006] Furthermore, the organic solvent in step (1) is any one of N-methylpyrrolidone, dimethylformamide, dimethylacetamide and dimethyl sulfoxide.
[0007] Furthermore, the viscosity of the polyamic acid solution in step (1) is 20000 mPa·s to 120000 mPa·s.
[0008] Furthermore, the solid content of the polyamic acid solution in step (1) is 10-20%.
[0009] Furthermore, the temperature of the cold water bath in step (1) is 0-15°C.
[0010] Furthermore, the stirring speed in step (1) is 500 to 2000 r / min.
[0011] Furthermore, in step (1), S-BPDA is finally added to adjust the viscosity, and then the mixture is placed in a cold water bath and stirred for reaction for 3 to 8 hours to obtain a polyamic acid solution.
[0012] Furthermore, in step (2), the polyamic acid solution obtained in step (1) is evenly coated on a clean glass plate by an automatic coating machine, and then placed in a forced air drying oven and treated at 160°C for 10 minutes to evaporate and remove the solvent. The glass plate is then placed in a forced air drying oven and heated according to the following procedure for thermal imidization: from 160°C to 210°C after 30 minutes and kept warm for 5 minutes, from 210°C to 260°C after 30 minutes and kept warm for 5 minutes, and finally raised to 400°C and kept warm for 5 minutes before cooling. After naturally cooling to room temperature, the glass plate is soaked in 100°C hot water for 20 minutes, and then the film is removed from the glass plate and dried to obtain a high Tg polyimide film.
[0013] Furthermore, the thickness of the high Tg polyimide film in step (2) is 20±5 μm.
[0014] Compared with the prior art, this technical solution has the following beneficial effects: 1. Since the glass transition temperature of polyimide film is directly related to the flexibility of molecular chain, the greater the flexibility of molecular chain, the lower the glass transition temperature; the greater the rigidity of molecular chain, the higher the glass transition temperature. And high Tg is usually caused by the combined effect of main chain rigidity and linearity and the accompanying high chain alignment along the plane of film. Therefore, the present invention adopts multi-polymerization method to introduce strong intermolecular interaction into polyimide (PI) molecular chain to synthesize high glass transition temperature (Tg) polyimide film, and the prepared high Tg polyimide film has very high tensile strength, elongation at break and high Tg, which provides important guarantee for the preparation of high Tg and high tensile strength polyimide film. The present invention uses p-phenylenediamine (PDA) with a rigid structure, pyromellitic anhydride (PMDA) with a highly symmetrical molecular structure, a diamine monomer containing a biphenyl structure, 4,4'-diamino-2,2'-dimethylbiphenyl (M-tol), and a dianhydride monomer containing a biphenyl structure, 3,3',4,4'-biphenyltetracarboxylic anhydride (S-BPDA). In order to ensure the successful preparation of the film, an appropriate amount of a diamine monomer containing a flexible ether bond, 4,4'-diaminodiphenyl ether (ODA), is also added.
[0015] 2. The p-phenylenediamine (PDA) used in the present invention is a rigid molecular chain that is conducive to obtaining a higher packing density, and can effectively reduce the free volume fraction so that the prepared PI film obtains a higher glass transition temperature; the pyromellitic dianhydride (PMDA) monomer has a typical linear skeleton structure, the molecular chain is highly symmetrical and rigid, and it is easier to orient in the plane to form a complete arrangement to obtain a lower CTE; the 4,4'-diamino-2,2'-dimethylbiphenyl (M-tol) diamine monomer contains a biphenyl structure, and the introduction of the biphenyl structure can increase the elastic modulus of the PI film. The monomer containing the biphenyl structure The molecular chain is straighter and the intermolecular force is stronger. The introduction of the biphenyl structure reduces the single bonds for internal rotation, and the side substituents increase the steric hindrance of molecular movement, making the arrangement of the molecular chain more regular, resulting in the PI film having a high degree of in-plane orientation, which can significantly reduce the thermal expansion coefficient (CTE) of PI; 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) also has a biphenyl structure, which can increase the molecular chain length of the prepared PI film, and improve the tensile strength and elongation at break of the film; 4,4'-diaminodiphenyl ether (ODA) contains a flexible ether bond that can increase the elongation at break of the PI film.
[0016] 3. The high Tg polyimide composite film prepared by the present invention has balanced mechanical properties, and the high Tg polyimide film has balanced mechanical properties, with a tensile strength of 187 MPa, an elongation at break of 38.1%, a modulus of 3.6 GPa, and a glass transition temperature of 540°C, and can be applied to the field of flexible packaging. DETAILED DESCRIPTION
[0017] The present invention is further described by the following examples, but is not intended to be limiting of the present invention. Specific experimental conditions and methods not specified in the following examples are conventional methods commonly known to those skilled in the art.
[0018] Embodiment 1: A method for preparing a five-component copolymer high Tg polyimide film, comprising the following steps: (1) weighing raw materials (including 1.2250 g of p-phenylenediamine) according to the molar ratio of p-phenylenediamine (PDA), pyromellitic dianhydride (PMDA), 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE), 4,4'-diaminodiphenyl ether (ODA) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) of 1.1:4.8:2.8:1.55:0.58 and placing them in an oven for drying respectively; dividing pyromellitic dianhydride (PMDA) into three parts of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C, and the mass ratio of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C is 2:3:5; Take p-phenylenediamine (PDA) and dissolve it in 100 mL of organic solvent and stir for 15 minutes to obtain a diamine monomer solution. Add dianhydride monomer A to the diamine monomer solution and stir and mix for 0.5 hours to obtain a mixed solution (no obvious particles exist in the mixed solution, and PDA and PMDA have been completely reacted). Then, add 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE) to the mixed solution and stir and mix for 0.5 hours (the color of the mixed solution changes from light green to turbid white), then add dianhydride monomer C and stir and mix for 0.5 hours (the color of the solution changes from turbid white to yellow), then add 4,4'-diaminodiphenyl ether (ODA) and stir and mix for 0.5 hours, then add dianhydride monomer B and stir and mix for 0.5 hours, finally add 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) to adjust the viscosity, and place it in a cold water bath and stir and react for 6 hours to obtain a polyamic acid solution (PAA); The organic solvent is dimethylacetamide; the viscosity of the polyamic acid solution is 55000 mPa·s; the solid content of the polyamic acid solution is 20%; the temperature of the cold water bath is 10° C.; the stirring speed is 1500 r / min; (2) The polyamic acid solution obtained in step (1) is uniformly coated on a clean glass plate by an automatic coating machine, and then placed in a forced air drying oven at 160°C for 10 minutes to evaporate and remove the solvent, and then the glass plate is continued to be placed in the forced air drying oven and heated according to the following program for thermal imidization process: from 160°C to 210°C after 30 minutes and kept warm for 5 minutes, from 210°C to 260°C after 30 minutes and kept warm for 5 minutes, and finally raised to 400°C and kept warm for 5 minutes before cooling, and after naturally cooling to room temperature, the glass plate is soaked in 100°C hot water for 20 minutes, and then the film is removed from the glass plate and dried to obtain a high Tg polyimide film; the thickness of the high Tg polyimide film is 15 μm.
[0019] Embodiment 2: A method for preparing a five-component copolymer high Tg polyimide film, comprising the following steps: (1) weighing raw materials (including 1.1815 g of p-phenylenediamine) according to the molar ratio of p-phenylenediamine (PDA), pyromellitic dianhydride (PMDA), 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE), 4,4'-diaminodiphenyl ether (ODA) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) of 1.09:4.9:2.7:1.6:0.6 and placing them in an oven for drying respectively; dividing pyromellitic dianhydride (PMDA) into three parts of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C, and the mass ratio of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C is 2:3:5; Take p-phenylenediamine (PDA) and dissolve it in 100 mL of organic solvent and stir for 15 minutes to obtain a diamine monomer solution. Add dianhydride monomer A to the diamine monomer solution and stir and mix for 0.5 hours to obtain a mixed solution (no obvious particles exist in the mixed solution, and PDA and PMDA have been completely reacted). Then, add 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE) to the mixed solution and stir and mix for 0.5 hours (the color of the mixed solution changes from light green to turbid white), then add dianhydride monomer C and stir and mix for 0.5 hours (the color of the solution changes from turbid white to yellow), then add 4,4'-diaminodiphenyl ether (ODA) and stir and mix for 0.5 hours, then add dianhydride monomer B and stir and mix for 0.5 hours, finally add 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) to adjust the viscosity, place it in a cold water bath and stir and react for 5 hours to obtain a polyamic acid solution (PAA); The organic solvent is dimethylformamide; the viscosity of the polyamic acid solution is 36000 mPa·s; the solid content of the polyamic acid solution is 18%; the temperature of the cold water bath is 8° C.; the stirring speed is 1200 r / min; (2) The polyamic acid solution obtained in step (1) is uniformly coated on a clean glass plate by an automatic coating machine, and then placed in a forced air drying oven at 160°C for 10 minutes to evaporate and remove the solvent, and then the glass plate is continued to be placed in the forced air drying oven and heated according to the following program for thermal imidization process: from 160°C to 210°C after 30 minutes and kept warm for 5 minutes, from 210°C to 260°C after 30 minutes and kept warm for 5 minutes, and finally raised to 400°C and kept warm for 5 minutes before cooling, and after naturally cooling to room temperature, the glass plate is soaked in 100°C hot water for 20 minutes, and then the film is removed from the glass plate and dried to obtain a high Tg polyimide film; the thickness of the high Tg polyimide film is 20 μm.
[0020] Embodiment 3: A method for preparing a five-component copolymer high Tg polyimide film, comprising the following steps: (1) weighing raw materials (including 1.1410 g of p-phenylenediamine) according to the molar ratio of p-phenylenediamine (PDA), pyromellitic dianhydride (PMDA), 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE), 4,4'-diaminodiphenyl ether (ODA) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) of 1.2:4.68:2.6:1.6:2.6 and placing them in an oven for drying respectively; dividing pyromellitic dianhydride (PMDA) into three parts of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C, and the mass ratio of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C is 2:3:5; Take p-phenylenediamine (PDA) and dissolve it in 100 mL of organic solvent and stir for 15 minutes to obtain a diamine monomer solution. Add dianhydride monomer A to the diamine monomer solution and stir and mix for 0.5 hours to obtain a mixed solution (no obvious particles exist in the mixed solution, and PDA and PMDA have been completely reacted). Then, add 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE) to the mixed solution and stir and mix for 0.5 hours (the color of the mixed solution changes from light green to turbid white), then add dianhydride monomer C and stir and mix for 0.5 hours (the color of the solution changes from turbid white to yellow), then add 4,4'-diaminodiphenyl ether (ODA) and stir and mix for 0.5 hours, then add dianhydride monomer B and stir and mix for 0.5 hours, finally add 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) to adjust the viscosity, and place it in a cold water bath and stir and react for 4 hours to obtain a polyamic acid solution (PAA); The organic solvent is dimethylformamide; the viscosity of the polyamic acid solution is 25000 mmPa·s; the solid content of the polyamic acid solution is 15%; the temperature of the cold water bath is 10° C.; the stirring speed is 1600 r / min; (2) The polyamic acid solution obtained in step (1) is uniformly coated on a clean glass plate by an automatic coating machine, and then placed in a forced air drying oven at 160°C for 10 minutes to evaporate and remove the solvent, and then the glass plate is continued to be placed in the forced air drying oven and heated according to the following program for thermal imidization process: from 160°C to 210°C after 30 minutes and kept warm for 5 minutes, from 210°C to 260°C after 30 minutes and kept warm for 5 minutes, and finally raised to 400°C and kept warm for 5 minutes before cooling, and after naturally cooling to room temperature, the glass plate is soaked in 100°C hot water for 20 minutes, and then the film is removed from the glass plate and dried to obtain a high Tg polyimide film; the thickness of the high Tg polyimide film is 18 μm.
[0021] Embodiment 4: A method for preparing a five-component copolymer high Tg polyimide film, comprising the following steps: (1) weighing raw materials (including 1.3350 g of p-phenylenediamine) according to the molar ratio of p-phenylenediamine (PDA), pyromellitic dianhydride (PMDA), 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE), 4,4'-diaminodiphenyl ether (ODA) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) of 1.0:4:2:1.5:0.5 and placing them in an oven for drying respectively; dividing pyromellitic dianhydride (PMDA) into three parts of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C, and the mass ratio of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C is 2:3:5; Take p-phenylenediamine (PDA) and dissolve it in 100 mL of organic solvent and stir for 15 minutes to obtain a diamine monomer solution. Add dianhydride monomer A to the diamine monomer solution and stir and mix for 0.5 hours to obtain a mixed solution (no obvious particles exist in the mixed solution, and PDA and PMDA have been completely reacted). Then, add 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE) to the mixed solution and stir and mix for 0.5 hours (the color of the mixed solution changes from light green to turbid white), then add dianhydride monomer C and stir and mix for 0.5 hours (the color of the solution changes from turbid white to yellow), then add 4,4'-diaminodiphenyl ether (ODA) and stir and mix for 0.5 hours, then add dianhydride monomer B and stir and mix for 0.5 hours, finally add 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) to adjust the viscosity, and place it in a cold water bath and stir and react for 3 hours to obtain a polyamic acid solution (PAA); The organic solvent is N-methylpyrrolidone; the viscosity of the polyamic acid solution is 120000 mPa·s; the solid content of the polyamic acid solution is 10%; the temperature of the cold water bath is 15° C.; the stirring speed is 500 r / min; (2) The polyamic acid solution obtained in step (1) is uniformly coated on a clean glass plate by an automatic coating machine, and then placed in a forced air drying oven at 160°C for 10 minutes to evaporate and remove the solvent, and then the glass plate is continued to be placed in the forced air drying oven and heated according to the following program for thermal imidization process: from 160°C to 210°C after 30 minutes and kept warm for 5 minutes, from 210°C to 260°C after 30 minutes and kept warm for 5 minutes, and finally raised to 400°C and kept warm for 5 minutes before cooling, and after naturally cooling to room temperature, the glass plate is soaked in 100°C hot water for 20 minutes, and then the film is removed from the glass plate and dried to obtain a high Tg polyimide film; the thickness of the high Tg polyimide film is 25 μm.
[0022] Embodiment 5: A method for preparing a five-component copolymer high Tg polyimide film, comprising the following steps: (1) weighing raw materials (including 1.2850 g of p-phenylenediamine) according to the molar ratio of p-phenylenediamine (PDA), pyromellitic dianhydride (PMDA), 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE), 4,4'-diaminodiphenyl ether (ODA) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) of 1.5:5:3:1.8:3 and placing them in an oven for drying respectively; dividing pyromellitic dianhydride (PMDA) into three parts of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C, and the mass ratio of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C is 2:3:5; Take p-phenylenediamine (PDA) and dissolve it in 100 mL of organic solvent and stir for 15 minutes to obtain a diamine monomer solution. Add dianhydride monomer A to the diamine monomer solution and stir and mix for 0.5 hours to obtain a mixed solution (no obvious particles exist in the mixed solution, and PDA and PMDA have been completely reacted). Then, add 4,4'-diamino-2,2'-dimethylbiphenyl (M-TOLIDINE) to the mixed solution and stir and mix for 0.5 hours (the color of the mixed solution changes from light green to turbid white), then add dianhydride monomer C and stir and mix for 0.5 hours (the color of the solution changes from turbid white to yellow), then add 4,4'-diaminodiphenyl ether (ODA) and stir and mix for 0.5 hours, then add dianhydride monomer B and stir and mix for 0.5 hours, finally add 3,3',4,4'-biphenyltetracarboxylic dianhydride (S-BPDA) to adjust the viscosity, place it in a cold water bath and stir and react for 8 hours to obtain a polyamic acid solution (PAA); The organic solvent is dimethylformamide; the viscosity of the polyamic acid solution is 60000 mPa·s; the solid content of the polyamic acid solution is 20%; the temperature of the cold water bath is 0°C; the stirring speed is 2000 r / min; (2) The polyamic acid solution obtained in step (1) is uniformly coated on a clean glass plate by an automatic coating machine, and then placed in a forced air drying oven at 160°C for 10 minutes to evaporate and remove the solvent, and then the glass plate is continued to be placed in the forced air drying oven and heated according to the following program for thermal imidization process: from 160°C to 210°C after 30 minutes and kept warm for 5 minutes, from 210°C to 260°C after 30 minutes and kept warm for 5 minutes, and finally raised to 400°C and kept warm for 5 minutes before cooling, and after naturally cooling to room temperature, the glass plate is soaked in 100°C hot water for 20 minutes, and then the film is removed from the glass plate and dried to obtain a high Tg polyimide film; the thickness of the high Tg polyimide film is 22 μm.
[0023] Comparative Example 1: Preparation of PMDA-PDA-ODA-M-tol-PI film, specifically comprising the following steps: S1: Weigh 1.2480g PDA and dissolve it in 100mL dimethylacetamide to obtain a uniform transparent solution of diamine; after stirring at 1500r / min for 15 minutes, add 2.3000g PMDA and continue to react for 0.5 hour, then continue to add 6.1284g M-TOLIDINE, stir at 1500r / min for 15 minutes, then add 5.7000g PMDA, then add 3.4663g ODA and stir at 1500r / min for 15 minutes, then add 4.0001g PMDA; then add 0.5859g PMDA as a solution viscosity adjustment, react in an ice water bath at 10℃ for 6 hours, and obtain PMDA-PDA-ODA-M-tol polyamide acid solution; S2: A PMDA-PDA-ODA-M-tol polyamic acid solution with a solid content of 20% was evenly coated on a glass plate, placed in a forced air drying oven, heated from 160 °C to 210 °C over 30 min and kept warm for 5 min, then heated from 210 °C to 260 °C over 30 min and kept warm for 5 min, finally heated to 400 °C and kept warm for 5 min before starting to cool down, naturally cooled to room temperature, soaked the glass plate in hot water for 20 minutes, and then removed the film from the glass plate. The thickness of the PMDA-PDA-ODA-M-tol-PI film was about 20 μm.
[0024] Comparative Example 2: Preparation of PMDA-S-BPDA-PDA-ODA-PI film, specifically comprising the following steps: S1: 3.0865 g PDA was weighed and dissolved in 100 mL dimethylacetamide to obtain a uniform transparent solution of diamine; after stirring at 1500 r / min for 15 minutes, 5.7000 g PMDA was added and the reaction continued for 0.5 hour, and then 5.0352 g ODA was added, and the mixture was stirred at 1500 r / min for 15 minutes, and then 5.5000 g PMDA was added, and the remaining PMDA was added to adjust the viscosity of the solution, and the mixture was reacted in an ice-water bath at 10°C for 6 hours to obtain a PMDA-S-BPDA-PDA-ODA polyamic acid solution, and the viscosity of the prepared PAA solution was 40000 mPa·s; S2: A PMDA-S-BPDA-PDA-ODA polyamide acid solution with a solid content of 20% was evenly coated on a glass plate, placed in a forced air drying oven, heated from 160 °C to 210 °C after 30 min and kept warm for 5 min, then heated from 210 °C to 260 °C after 30 min and kept warm for 5 min, finally heated to 400 °C and kept warm for 5 min before starting to cool down, naturally cooled to room temperature, soaked the glass plate in hot water for 20 minutes, and then removed the film from the glass plate. The thickness of the PMDA-S-BPDA-PDA-ODA-PI film was about 20 μm.
[0025] Comparative Example 3: Preparation of PMDA-S-BPDA-PDA-M-tol-PI film, specifically comprising the following steps: S1: Weigh 3.0419 g PDA and dissolve it in 100 mL dimethylacetamide to obtain a uniform transparent solution of diamine; after stirring at 1500 r / min for 15 minutes, add 5.5700 g PMDA and continue to react for 0.5 hour, then continue to add 5.9715 g M-TOLIDINE, stir at 1500 r / min for 15 minutes, add 5.5800 g PMDA and add the remaining PMDA to adjust the solution viscosity, react in an ice-water bath at 10°C for 6 hours to obtain PMDA-S-BPDA-PDA-M-tol polyamic acid solution, and the prepared PAA solution has a viscosity of 15000 mPa·s; S2: A PMDA-S-BPDA-PDA-M-tol polyamic acid solution with a solid content of 20% was evenly coated on a glass plate, placed in a forced air drying oven, heated from 160 °C to 210 °C after 30 min and kept warm for 5 min, then heated from 210 °C to 260 °C after 30 min and kept warm for 5 min, finally heated to 400 °C and kept warm for 5 min before starting to cool down, naturally cooled to room temperature, soaked the glass plate in hot water for 20 minutes, and then removed the film from the glass plate. The thickness of the PMDA-S-BPDA-PDA-M-tol-PI film was about 20 μm.
[0026] Comparative Example 4: Preparation of S-BPDA-PDA-ODA-M-tol-PI film, specifically comprising the following steps: S1: Weigh 1.0510g PDA and dissolve it in 100mL dimethylacetamide to obtain a uniform transparent solution of diamine; after stirring at 1500r / min for 15 minutes, add 2.8002g S-BPDA and continue to react for 0.5 hours, then continue to add 5.1579g M-TOLIDINE, stir at 1500r / min for 15 minutes, and then add 6.5003g S-BPDA; then add 2.9191g ODA, and then add 0.9970g S-BPDA. The remaining S-BPDA is added to adjust the viscosity of the solution, and react in an ice-water bath at 10℃ for 6 hours to obtain S-BPDA-PDA-ODA-M-tol polyamic acid solution. The viscosity of the prepared PAA solution is 25000mpa·s; S2: A S-BPDA-PDA-ODA-M-tol polyamic acid solution with a solid content of 20% was evenly coated on a glass plate, placed in a forced air drying oven, heated from 160 °C to 210 °C after 30 min and kept warm for 5 min, then heated from 210 °C to 260 °C after 30 min and kept warm for 5 min, finally heated to 400 °C and kept warm for 5 min before starting to cool down, naturally cooled to room temperature, soaked the glass plate in hot water for 20 minutes, and then removed the film from the glass plate. The thickness of the obtained S-BPDA-PDA-ODA-M-tol-PI film was about 20 μm.
[0027] Comparative Example 5: Preparation of PMDA-ODPA-PDA-M-tol-ODA-PI film, specifically comprising the following steps: S1: Weigh 1.1209 gPDA and dissolve it in 100 mL of dimethylacetamide to obtain a uniform transparent solution of diamine; after stirring at 1500 r / min for 15 minutes, add 2.9098 gODPA and continue to react for 0.5 hour, then continue to add 5.5009 gM-TOLIDINE, stir at 1500 r / min for 15 minutes, then add 5.1038 gODPA and continue to react for 0.5 hour; then add 2.6715 gODA and stir at 1500 r / min for 15 minutes, then add 4.6189 gPMDA; then add the remaining PMDA as a solution viscosity adjustment, react in an ice water bath at 10°C for 6 hours, and obtain PMDA-ODPA-PDA-M-ol-ODA polyamic acid solution, the viscosity of the prepared PAA solution is 15000 mpa·s; S2: A PMDA-ODPA-PDA-M-ol-ODA polyamic acid solution with a solid content of 20% was evenly coated on a glass plate, placed in a forced air drying oven, heated from 160 °C to 210 °C after 30 min and kept warm for 5 min, then heated from 210 °C to 260 °C after 30 min and kept warm for 5 min, finally heated to 400 °C and kept warm for 5 min before starting to cool down, cooled naturally to room temperature, soaked the glass plate in hot water for 20 minutes, and then removed the film from the glass plate. The thickness of the PMDA-ODPA-PDA-M-ol-ODAPI film was about 20 μm.
[0028] Comparative Example 6: Preparation of BPDA-ODPA-PDA-ODA-M-Tol-PI film, specifically comprising the following steps: S1: Weigh 1.0338 gPDA and dissolve it in 100 mL of dimethylacetamide to obtain a uniform transparent solution of diamine; after stirring at 1500 r / min for 15 minutes, add 2.9098 gODPA and continue to react for 0.5 hours, then continue to add 5.0738 gM-TOLIDINE, stir at 1500 r / min for 15 minutes, then add 7.0319 gODPA, then add 2.8715 gODA1500 r / min and stir for 15 minutes, then add 4.0189 gS-BPDA; then add the remaining S-BPDA to adjust the solution viscosity, react in an ice water bath at 10°C for 6 hours, and obtain BPDA-ODPA-PDA-ODA-M-Tol polyamic acid solution; S2: A BPDA-ODPA-PDA-ODA-M-Tol polyamic acid solution with a solid content of 20% was evenly coated on a glass plate, placed in a forced air drying oven, heated from 160 °C to 210 °C after 30 min and kept warm for 5 min, then heated from 210 °C to 260 °C after 30 min and kept warm for 5 min, finally heated to 400 °C and kept warm for 5 min before starting to cool down, naturally cooled to room temperature, soaked the glass plate in hot water for 20 minutes, and then removed the film from the glass plate. The thickness of the obtained BPDA-ODPA-PDA-ODA-M-Tol-PI film was about 20 μm.
[0029] Experimental Example: Films were prepared according to the methods described in Examples 1 to 5 and Comparative Examples 1 to 6, and all films were tested for mechanical properties, water absorption and glass transition temperature. The specific results are shown in Table 1. The thickness of the high Tg polyimide films prepared according to Examples 1 to 5 of the present invention was about 20 μm, and the glass transition temperature was 511.37 to 544.11°C, which were higher than the comparative example, indicating that the high Tg polyimide film of the present invention has good thermal stability and high temperature resistance, and the film obtained by the present invention has good mechanical properties, high tensile strength and elongation at break, elastic modulus of 3.6 to 4.2 GPa, tensile strength of 187 to 201 MPa, and elongation at break of 38.1 to 45.5%.
[0030] Table 1 Performance test results of films prepared by different methods
[0031] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a five-component copolymer high Tg polyimide film, characterized in that: The following steps are involved: (1) weighing raw materials according to the molar ratio of p-phenylenediamine, pyromellitic dianhydride, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diaminodiphenyl ether and 3,3',4,4'-biphenyltetracarboxylic dianhydride of (1.0-1.5):(4-5):(2-3):(1.5-1.8):(0.5-3) and placing them in an oven for drying respectively; dividing pyromellitic dianhydride into three parts: dianhydride monomer A, dianhydride monomer B and dianhydride monomer C, and the mass ratio of dianhydride monomer A, dianhydride monomer B and dianhydride monomer C is 2:3:5; Dissolve p-phenylenediamine in an organic solvent and stir to obtain a diamine monomer solution, add dianhydride monomer A to the diamine monomer solution, stir and react for 0.5 hours to obtain a mixed solution, then add 4,4'-diamino-2,2'-dimethylbiphenyl to the mixed solution, stir and react for 0.5 hours, then add dianhydride monomer C, stir and react for 0.5 hours, then add 4,4'-diaminodiphenyl ether, stir and react for 0.5 hours, then add dianhydride monomer B, stir and react for 0.5 hours, finally add 3,3',4,4'-biphenyltetracarboxylic dianhydride to adjust the viscosity, and place in a cold water bath and stir to react to obtain a polyamic acid solution; (2) The polyamic acid solution obtained in step (1) is coated on a glass plate, and then the temperature is increased for thermal imidization to obtain a high Tg polyimide film.
2. The method for preparing a five-component copolymer high Tg polyimide film according to claim 1, characterized in that: The organic solvent in step (1) is any one of N-methylpyrrolidone, dimethylformamide, dimethylacetamide and dimethyl sulfoxide.
3. The method for preparing the five-component copolymer high Tg polyimide film according to claim 1, characterized in that: The viscosity of the polyamic acid solution in step (1) is 20000 mPa·s to 120000 mPa·s.
4. The method for preparing a five-component copolymer high Tg polyimide film according to claim 1, characterized in that: The solid content of the polyamic acid solution in step (1) is 10-20%.
5. The method for preparing a five-component copolymer high Tg polyimide film according to claim 1, characterized in that: The temperature of the cold water bath in step (1) is 0-15°C.
6. The method for preparing the five-component copolymer high Tg polyimide film according to claim 1, characterized in that: The stirring speed in step (1) is 500-2000 r / min.
7. The method for preparing the five-component copolymer high Tg polyimide film according to claim 1, characterized in that: In step (1), S-BPDA is finally added to adjust the viscosity, and the mixture is placed in a cold water bath and stirred for reaction for 3 to 8 hours to obtain a polyamic acid solution.
8. The method for preparing a five-component copolymer high Tg polyimide film according to claim 1, characterized in that: In step (2), the polyamic acid solution obtained in step (1) is evenly coated on a clean glass plate by an automatic coating machine, and then placed in a forced air drying oven and treated at 160°C for 10 minutes to evaporate and remove the solvent. The glass plate is then placed in a forced air drying oven and heated according to the following procedure for thermal imidization: from 160°C to 210°C after 30 minutes and kept warm for 5 minutes, from 210°C to 260°C after 30 minutes and kept warm for 5 minutes, and finally raised to 400°C and kept warm for 5 minutes before cooling. After naturally cooling to room temperature, the glass plate is soaked in 100°C hot water for 20 minutes, and then the film is removed from the glass plate and dried to obtain a high Tg polyimide film.
9. The method for preparing a five-component copolymer high Tg polyimide film according to claim 1, characterized in that: The thickness of the high Tg polyimide film in step (2) is 20±5 μm.
10. A five-component copolymer high Tg polyimide film obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Low-dielectric polyimide film and preparation method thereof
CN114616269A
Polyamic acid composition, polyimide, polyimide film and method for producing them
JP2012153806A
Polyimide laminate
JP2024066870A
Polyimide film, method for producing same, and flexible metal foil clad laminate comprising same
US20230049631A1
Multilayer polyimide film
WO2024085047A1
